PENGGUNAAN UJARAN DAN EKSPRESI EMOSIONAL DALAM MENGEKSPRESIKAN KEMARAHAN DALAM FILM JOKER KARYA TODD PHILLIPS (ANALISIS PSIKOLINGUISTIK) - Usuli, Nurlia T.; Lasut, Theresia M.C; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT     This research entitled “Penggunaan Ujaran dan Ekspresi Emosional dalam Mengekspresikan Kemarahan dalam Film Joker Karya Todd Phillips (Analisis Psikolinguistik). This research focuses on identifying and classifying the utterances in expressing anger, and analyzing the emotional expressions. There are two types of communiactios, which are verbal communication and non verbal communication. Utterances are the verbal communication while the emotional expression is the nonverbal communication. The form of the utterance divided into several, such as emotive speech, phatic speech, conative speech, referential speech, metalingual speech, and phoetic speech. Emotional expressions that can be realized are facial expressions, voice, gesture, and posture. Face and voice can describe a person’s emotional state. It can be extinguished between people who are in a state of emotion and the other from a change of voice and facial expressions. The gesture and posture are physical actions appear to communicate a certain message. The researcher used descriptive method in order to find out the use of utterance and emotional expressions in film Joker as the data supported by Jakobson (1960) and Plutchik’s (2003) theory. The results of this research show that the utterances that express the anger can be seen in the act of speech by the characters, such as emotive speech, conative speech, and referential speech. While the emotional expression can be seen in several ways, such as face expressions, posture and gesture, tone of voice, physiological changes, and emotional actions, like the eyes staring intently at someone, frowning forehead, squinting or bulging eyes, hold the gun, lips tightly closed, jaws tighten, high and firm tone of voice, sweating, shouting, punching at each other in the face, index finger pointing, body leaning and stiff.-------------------------------------------------------Keywords : Utterances, Emotional Expression, Anger, Film Joker, Psycholinguistics